ANALISIS REVISI UNDANG-UNDANG NOMOR 2 TAHUN 2021 TENTANG OTONOMI KHUSUS PAPUA DAN IMPLIKASINYA TERHADAP KEHADIRAN ORANG ASLI PAPUA DALAM MENGATUR DAERAH OTONOMI BARU - Muhammad Apriliansyah (2023)
concerning the Special Autonomy of Papua and its Implications for the Presence of Indigenous Papuans in Regulating the New Autonomous Region. Amendment to Law Number 2 of 2021 concerning Special Autonomy for Papua, in particular article 76, indirectly eliminates the authority of the Papuan legislative bodies, namely the DPRP and MRP in terms of dividing the Papua region and the Central Government has full authority to divide the Papua region without waiting for the approval of the MRP and DPRP, so indirectly this has weakened or even eliminated the political rights of Indigenous Papuans in governing the new autonomous region. The method used in this research is descriptive qualitative with narrative and discourse analysis using primary and secondary data including interviews, documentation, and literature study. The author also uses four stages of data analysis including data collection, data reduction, data presentation, and drawing conclusions. The results obtained from this study indicate that there has been a centralization effort from the Central Government in suppressing separatist movements in Papua by adding security personnel which is in line with the division of the Province in Papua. The Central Government considers that the performance of the MRP during the implementation of the Special Autonomy for Papua from 2001 to 2021 has not been maximized, and that there is a need for Central Government intervention so that the development that is taking place in Papua runs smoothly. The process of drafting changes to Law Number 2 of 2021 itself does not involve the participation of the MRP and DPRP as legislative and cultural representative institutions of the OAP that are recognized by the state, which causes the loss of the political meaning of presence which was the initial goal in Law Number 21 of 2001 concerning Special Autonomy for Papua. The critical policy analysis that the author conducted on the policy of Law Number 2 of 2021 concerning Special Autonomy for Papua considers that the Central Government uses its power to benefit and Indigenous Papuans are ignored because they do not have the opportunity to formulate policies for their own territory.